Ionic Liquids Chemical Stress Triggers Sphingoid Base Accumulation in Aspergillus nidulans - Hartmann, Diego O.; Piontkivska, Daryna; Moreira, Carlos J. S.; Silva Pereira, Cristina (Frontiers in Microbiology, 2019)
Understanding stress responses and signaling pathways in fungi became a fundamental need for the discovery of new specific antifungal targets for fighting emerging life-threatening pathogens and drug resistance. Ionic liquids constitute a unique class of chemicals, which structural diversity and tunable physical and chemical properties can provide a great diversity of stimuli. In this study, we propose the use of ionic liquids as tools to unravel signaling of stress responses in the filamentous fungus Aspergillus nidulans. We assessed how three ionic liquids with distinct effects over the cell wall and plasma membrane affect the biosynthesis of sphingolipids and accumulation of free sphingoid bases in this fungus. The stress imposed by each ionic liquid triggered the sphingolipid biosynthetic pathway and led to distinct profiles of sphingoid bases accumulation. Dodecyltributylphosphonium chloride and 1 decyl 3 methylimidazolium chloride induced the accumulation of sphingosine and of a yet unknown sphingoid base, respectively, while cholinium decanoate did not seem to accumulate any of these intermediates. This study brings further light to the roles of sphingoid bases in A. nidulans. In particular, sphingosine as a possible response mediator to cell wall damage induced by dodecyltributylphosphonium chloride, and involvement of an unknown sphingoid base in the response to plasma membrane permeabilization caused by 1 decyl 3 methylimidazolium chloride. In addition, we completed the genetic assignment of the glucosylceramide pathway in A. nidulans through the identification of the sphingolipid Δ4-desaturase gene (AN4405). The knowledge established reinforces the idea of targeting sphingolipids biosynthesis in the search of improved antifungal compounds.